Until proven innocent : political correctness and the shameful injustices of the Duke lacrosse rape case - Taylor, Stuart, 1948-; Johnson, K. C. (New York : Thomas Dunne Books/St. Martin's Press, 2007)
The saga of the Duke lacrosse team members' alleged rape of an African-American stripper and the unraveling of the case against them. Covering all five aspects of the case (personal, legal, academic, political, and media), journalist Taylor and historian Johnson argue that law enforcement, a campaigning prosecutor, biased journalists, and left-leaning academics repeatedly refused to pursue the truth while scapegoats were made of these young men, recklessly tarnishing their lives. T
Includes index.
Keywords: Seligmann, Reade; Finnerty, Collin; Evans, David Forker, -- 1983-; Nifong, Michael Byron; Rape -- North Carolina -- Durham; Malicious accusation -- North Carolina -- Durham; Rape -- Investigation -- North Carolina -- Durham; Trials (Rape) -- North Carolina -- Durham; Lacrosse players -- North Carolina -- Durham; Prosecution -- Corrupt practices -- North Carolina -- Durham